High-School Students with High-Incidence Disabilities' Use of Smartphones for Self-Monitoring. Issue 4 (8th August 2022) - Cook, Kathleen B.; Sayeski, Kristin L.
ABSTRACT: Self-monitoring of attention (SMA) promotes increased learning opportunities and greater independence for students but has been sparsely researched with high-school students. This study evaluated the effects of a self-monitoring strategy that included the use of a smartphone with a vibrating app to signal high-school students with high-incidence disabilities to self-monitor on-task behavior in general education classrooms. A multiple-treatment research design was used to evaluate potential effects of this self-monitoring strategy on on-task behavior and then compare the effects of self-monitoring alone to self-monitoring with self-graphing. At least two of four participants showed moderate increases in on-task behavior when self-monitoring. Only two participants used self-graphing materials and neither showed additional increases in on-task behavior when self-graphing was used. Generalization across settings was not evident; however, treatment effects were maintained for five to seven weeks for two participants. End-of-study surveys indicated that participants and teachers found the self-monitoring intervention to be acceptable for general education settings.